ELECTRONIC MARKETPLACES AS A FORM OF ORGANIZATION OF TRADE IN ENTERPRISES - Strzębicki, Dariusz (Acta Scientiarum Polonorum. Oeconomia, 2016)
The aim of this article is to assess the impact of new information technologies, in particular electronic marketplaces on the conducted transactions and transaction costs incurred by enterprises. An important goal was also an attempt to evaluate the role of transaction cost economics in explaining the development of B2B electronic marketplaces. The dominant approach in the analysis of this problem in the article was the transaction costs economics. Electronic marketplaces are information systems, which reveal the effect of the electronic broker. However, the economic reality shows that electronic markets also allow the effect of electronic integration. Transaction cost theory is useful in explaining the impact of information technology on transactions between businesses but should also be complemented by the results of research and analysis of other scientific theories, such as resources based view.